If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3y + -5 = 13 Reorder the terms: -5 + -3y = 13 Solving -5 + -3y = 13 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -3y = 13 + 5 Combine like terms: -5 + 5 = 0 0 + -3y = 13 + 5 -3y = 13 + 5 Combine like terms: 13 + 5 = 18 -3y = 18 Divide each side by '-3'. y = -6 Simplifying y = -6
| 3x^6+23x^3+40= | | 4y-10x=60 | | 6x^4y^3+30x^4y^2-144x^4y= | | 7xy+9xy=28 | | 2x-7=40 | | 7x^5y^3+14x^5y^2-168x^5y= | | 830-60m=970-80m | | 5y+11= | | y+2x=18 | | 13x^3y^3+78x^3y^2-91x^3y= | | 7xy+9xy=21 | | -18-6k=6k(1+3k) | | (2x-5)(6x+5)=0 | | x^2+6=10 | | 5x-7=-91-9x | | -2(x-1)=2(x-1) | | 18x^2+22x=0 | | -18-2x=4x+9 | | 64-6x=9x+9 | | 6x-3y-(3x-7y)=0 | | X^2-1.5x+8=0 | | (-6x-11)-(2x-4)= | | 6t+20=8t-60 | | 2+c= | | m^4-5m^3+6m^2=0 | | 144=12a+60 | | 0.25(12+4x)-0.5(6+2x)= | | 15-4(3x+5y)= | | 6+y=4y-3 | | 55=-6x+7 | | 0.75=x+(1-x) | | 17=-12+f |